Determination of performance characteristics using FEA-analytical for outer rotor BLDC motor - Kamaroszaman, Saharudin; Othman, Raja Nor Firdaus Kashfi Raja; Karim, Kasrul Abdul; Ahmad, Suhairi Rizuan Che; Tashiro, Kunihisa (Institute of Advanced Engineering and Science, 2023)
This paper presents an analytical approach to determine the performance characteristics of an outer rotor Brushless DC (BLDC) motor using finite element analysis (FEA). An accurate performance characteristic is a crucial deliverable during the early motor design process in order to minimize the cost of change while delivering a feasible design to the application. There are several popular methods to determine motor performance, including template-based software as well as FEA. However, these two methods have limitations in terms of geometry and time. Therefore, this paper proposes that the limitations can be addressed by using a combination of FEA and mathematical equations. First, the optimum motor design is determined using an FEA analytical approach. Second, the torque constant KT, is derived from the FEA results and followed by performance curve generation using the mathematical equation of speed, current, and output power in terms of torque function. Finally, the outcome results are verified against the motor requirements, including an assessment of maximum speed, stall current, and maximum output power. In conclusion, this research introduces a methodology for determining full curve motor performance prior to prototype fabrication. The leverage benefit could be gained through robust design and low-cost development.